Aplikasi Mikrooganisme Lokal (MOL) Pelepah Kelapa Sawit terhadap Pertumbuhan Tanaman Pakcoy (Brassica rapa L.) - Febrianti Febrianti; Depita Sari; Nursyam Arrozi; Reiza Mutia AR (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
A common horticultural plant in Indonesia is the Pakcoy (Brassica rapa L.). Because of its low nutrient content, pakcoy output declines annually. By applying fertilizer, low nutrient levels can be raised. One such form of fertilizer is local microorganisms an organic fertilizer. Gibberellin, cytokinin, auxsin, and other phytohormones substances that promote plant growth and development as well as inhibitors that can boost plant activity and nutrition are all found in local microorganisms. Palm fronds, which are by products of the palm oil industry, are one type of organic material that can be utilized as local microorganisms. This study sought to ascertain the impact and optimal method of administering local microorganisms to oil palm fronds in order to promote growth and pakcoy plant output. The study employed a non factorial Randomized Block Design with 3 replications and 4 treatments. D0 (control), D1 (10 ml/polybag), D2 (15 ml/polybag), and D3 (20 ml/polybag) were the treatments. Plant height (cm), number of leaves (pieces), leaf breadth (cm), and wet weight (g) were the parameters used for the observation. The height and quantity of leaves of pakcoy plants are 2 growth characteristics that are impacted when oil palm fronds are given local microorganisms. With a concentration of 15 ml/polybag, treatment D2 produced the highest local microorganisms concentration of oil palm fronds.